Frequency of Arrhythmias in ST-Segment Elevation Myocardial Infarction Patients During Primary Percutaneous Coronary Intervention (PPCI) Till 48 hours Post PPCI in NICVD - Fawad Ali Siddiqui, Syed Khubaib, Harish Kumar, Haresh Kumar, Muhammad Aslam, Khushwant, Saif Ur Rehman, Yumna Siddiqui (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of arrhythmias in patients with acute ST-segment elevation myocardial infarction primary percutaneous coronary intervention (PPCI) till 48 hours post PPCI in admitted at national institute of cardiovascular diseases (NICVD), Karachi. Material & Methods: This was a hospital based clinical study conducted at NICVD through convenience sampling technique for the period of 6 months from 1st September 2021 to 31st March, 2022. All the adult (age more than 18 years) male and female, presented with acute ST-segment elevation myocardial infarction, and eligible for PPCI were included in this study. Cardiac arrhythmias during 48 hours post-PPCI were evaluated and documented. SPSS v. 26 was used for data entry and analysis. Results: A total of 285 patients were included for final analysis. The overall mean age ± SD was 56.56±13.07 years. Most of the patients were belongs to age group II (age ≥55 years) as compare to age group I (age <55 years), 50.87% and 49.12%, respectively. The overall incidence of arrhythmias was 16.6% among them most of the arrhythmias were observed during the first 24 hours of PPCI (72.22%). Ventricular arrhythmias were most common as compare to atrial arrhythmias (61.11%). There was an insignificant association observed in relation to gender and incidence of arrhythmias, p 0.236. Patients having age ≥55 were significantly associated with occurrence of arrhythmias, p <0.001. Conclusion: Frequency of cardiac arrhythmias is higher during early hours of after PPCI. Among them, ventricular arrhythmias were more common as compare to atrial arrhythmias. Older patients (age >55 years) were significantly associated with increased incidence of cardiac arrhythmias as compare to younger age group (age <55 years). Keywords: Cardiac arrhythmias, STEMI, primary PCI, time duration, in-hospital incidence, South Asia